Occurrence of Enterococci in the Process of Artisanal Cheesemaking and Their Antimicrobial Resistance - Hanzelová, Zuzana; Dudriková, Eva; Lovayová, Viera; Výrostková, Jana; Regecová, Ivana; Zigo, František; Bartáková, Klára (Life (Basel, Switzerland), 2024)
Enterococci are a group of microorganisms that have a controversial position from some scientific points of view. The species of the greatest clinical importance are E. faecalis and E. faecium, which are common agents of nosocomial infections. However, enterococci also have important applications in the dairy industry, as they are used as non-starter lactic acid bacteria (NSLAB) in a variety of cheeses, especially artisanal cheeses. The aim of this study was to determine the presence of representatives from the Enterococcus genus using PCR and MALDI-TOF MS methods on samples of raw milk, processing environment swabs, and cheese from four different artisanal dairy plants in Slovakia. Among the 136 isolates of enterococci, 9 species of genus Enterococci (E. faecalis, E. faecium, E. durans, E. devriesi, E. hirae, E. italicus, E. casseliflavus, E. malodoratus, and E. gallinarum) were identified and were tested for their antimicrobial resistance (AMR) to 8 antibiotics (amoxicillin, penicillin, ampicillin, erythromycin, levofloxacin, vancomycin, rifampicin, and tetracycline); most of them were resistant to rifampicin (35.3%), ampicillin (22.8%), and tetracycline (19.9%). A PCR analysis of vanA (4.41%) and tetM (14.71%) revealed that antimicrobial resistance genes were present in not only phenotypic resistant isolates of enterococci but also susceptible isolates. The investigation of antimicrobial resistance in enterococci during the cheesemaking process can be a source of valuable information for public health in the concept of "One Health".
Keywords: enterococcal isolates; processing environment; PCR; MALDI-TOF MS; silent genes